Identifikasi Hambatan dan Tantangan dalam Implementasi Alat Evaluasi Digital untuk Pembelajaran Bahasa Inggris di Kelas VI SD N 2 Siangan - Ni Kadek Intan Berliana Wati; Putu Beny Pradnyana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify obstacles and challenges in the application of digital evaluation tools for English learning in grade VI of SD Negeri 2 Siangan. The method used was qualitative descriptive research, with data collection through questionnaires and interviews involving 31 students and grade VI teachers. The results of the study showed that 85% of students felt an increase in learning motivation after using digital evaluation tools, although 40% of students experienced difficulties, especially related to limited internet access. Interviews with teachers revealed that they felt trained enough to utilize this tool effectively. Limited infrastructure and lack of training for teachers were identified as major challenges. Therefore, this study recommends the need to improve technology infrastructure and training programs for teachers to optimize the use of digital evaluation tools in English learning.